2019
DOI: 10.1111/brv.12570
|View full text |Cite
|
Sign up to set email alerts
|

Fungal functional ecology: bringing a trait‐based approach to plant‐associated fungi

Abstract: Fungi play many essential roles in ecosystems. They facilitate plant access to nutrients and water, serve as decay agents that cycle carbon and nutrients through the soil, water and atmosphere, and are major regulators of macro‐organismal populations. Although technological advances are improving the detection and identification of fungi, there still exist key gaps in our ecological knowledge of this kingdom, especially related to function. Trait‐based approaches have been instrumental in strengthening our und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
173
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(175 citation statements)
references
References 298 publications
(430 reference statements)
2
173
0
Order By: Relevance
“…Further research identifying variation in functional trait space and how it relates to ecological processes like dispersal will improve our understanding of mycorrhizal ecology (Zanne et al ., 2019). Unlike spore size, variation in melanization or spore ornamentation were not related to aerial AM fungal dispersal in our study and could not be compared broadly to all Glomeromycota due to a lack of available trait data for all described species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research identifying variation in functional trait space and how it relates to ecological processes like dispersal will improve our understanding of mycorrhizal ecology (Zanne et al ., 2019). Unlike spore size, variation in melanization or spore ornamentation were not related to aerial AM fungal dispersal in our study and could not be compared broadly to all Glomeromycota due to a lack of available trait data for all described species.…”
Section: Discussionmentioning
confidence: 99%
“…Because the outcome of AM symbioses can vary as fungal communities shift, studying AM fungal dispersal in cities has implications for efforts to improve urban sustainability (Chaudhary et al ., 2019). We also compare the measured traits of aerial spores to known traits for all described AM fungi present in the FUN FUN fungal functional trait database (Zanne et al ., 2019). We predict that aerial AM fungal spores will possess traits more conducive to wind dispersal, such as a smaller diameter than the average for all AM fungal species (Hypothesis 1).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results also underline this EM trait of organic N enzymatic processing (Bödeker et al, 2014) especially in those ectomycorrhiza descended from white rot as opposed to brown rot saprotrophic fungi (Stuart & Plett, 2020). Trait-based experimental design and analysis is increasingly recognized as a valuable method for characterizing guild differences (Lustenhouwer, Maynard, Bradford, Lindner, & Oberle, 2020;Mcgill, Enquist, Weiher, & Westoby, 2006;Zanne et al, 2020). Considering current projections of atmospheric CO2 increase, nitrogen deposition, phosphorus limitations, and the degradation and loss of forests worldwide (Crowther et al, 2016;Fitter, Heinemeyer, & Staddon, 2000;IPCC, 2014), clarifying the ecological function of mycorrhizal symbiosis is timely and relevant.…”
Section: Introductionmentioning
confidence: 87%
“…Here, we demonstrate that the difference in lifestyle between endophytic and ectomycorrhizal fungi could derive from functional diversity and genome content, respectively, despite both being associated with plants. Admittedly, the importance of the genome content of mycorrhizal fungi is questionable as the convergent evolution of the mycorrhizal habit occurred via the repeated evolution from saprotrophic ancestors (Kohler et al, 2015) but genomic sequencing revealed substantial variation between species from the same functional guild resulting in the analysis of trait-based approaches for understanding fungal activity instead of continuous classifications (Zanne et al, 2019). A trait-based approach to measure enzyme activity directly will be necessary when taxa do not fit into functional guilds (Peay et al, 2016).…”
Section: Genome Contentmentioning
confidence: 99%